Konseling Individual dengan Reinforcement Positif Untuk Meningkatkan Motivasi Belajar Siswa Broken home: Studi Kasus - Febriani, Nadila; Putri, Erika; Handayani, Fitri; Donal, Donal (Jurnal Bimbingan dan Konseling Pandohop, 2026)
Low learning motivation among students from broken homes forms the background of this study. This study aims to explain changes in students’ learning motivation after receiving individual counseling services using positive reinforcement techniques. This research employed a qualitative approach with a case study design, as the focus was directed at a single eighth-grade student exhibiting symptoms of low learning motivation. Data were collected through observation, interviews, and documentation. The findings indicate that low learning motivation was influenced by family disharmony, economic pressure, early-age responsibilities, and negative labeling from the school environment. The intervention consisted of five individual counseling sessions applying positive reinforcement, including verbal reinforcement, point-based reinforcement, and meaningful rewards. The results demonstrated improvements in students’ learning behaviors, including increased focus, greater responsibility for school assignments, improved politeness, active participation in classroom activities, and more regular school attendance. These findings confirm that positive reinforcement is an effective strategy for school counselors in supporting students from broken homes who experience decreased learning motivation.